X-ray tomography shows the varying three-dimensional morphology of gold nanoaggregates in the cellular ultrastructure. Issue 8 (17th June 2019) - Drescher, Daniela; Büchner, Tina; Guttmann, Peter; Werner, Stephan; Schneider, Gerd; Kneipp, Janina
Abstract : Soft X-ray tomography data were used for volume rendering of both cellular organelles and intracellular gold nanoparticle aggregates. They reveal variation in properties of the nanoaggregates with incubation time, cell type, and particle properties. Abstract : The processing of nanoparticles inside eukaryotic cells is a key step in many wanted and unwanted nano-bio-interactions. In order to understand the effects and functions of the intracellular aggregates that are formed, their properties and their interaction with the biological matrix must be characterized. High quality synchrotron soft X-ray tomography (SXT) data were obtained from cells containing gold nanoparticles that are commonly applied as tools for optical probing or drug delivery. 3D volume rendering of both cellular organelles and the nanoparticle aggregates of different sizes in the intact cells of two cell lines reveals variation in localization, size, shape and density of the intracellular gold nanoaggregates. The dependence of such variation on incubation time and cell type, as well as on the influence of pre-aggregation of primary nanoparticles is shown. The SXT results provide a detailed picture of intracellular aggregation and will improve the design of safe and efficient nanoparticle platforms for biomedical use.